A 20-Year Epidemiological Review of Testis Cancer at a French Military Hospital. Issue 11 (1st November 2015) - Dusaud, Marie; Durand, Xavier; Desfemmes, François-Régis; Molimard, Benoît; Bayoud, Younes; Audouin, Marie; Houlgatte, Alain
ABSTRACT: Objectives: To determine if the epidemiology of testis cancer in military service has followed worldwide trends and if the end of conscription in 2000 in France marked an epidemiologic turn. Methods: All of the patients who had an orchiectomy for a testis germ tumor from January 1990 to January 2011 were studied. The patients were divided into two groups: orchiectomy before 2000 and after 2000. Results: 289 patients were included, with a mean age of 30.8. The mean age at diagnosis increased significantly as well as the proportion of stage 1 seminomas, whereas stage 1 nonseminomatous germ cell tumors (NSGCT) slightly decreased. For stage 1 seminomas, there was an increase in the surveillance (10% vs. 31%) and in the number of chemotherapies (19% vs. 22%); for stage 1 NSGCT, surveillance also increased (53% vs. 64%). The specific 5-year survival was 98.3%. Conclusions: We noted an increase in the number of stage 1 seminomas, the surveillance of located germ tumors, and an excellent survival rate. However, the population was younger with regard to national data, and the number of stage 1 NSGCT decreased in favor of advanced metastatic tumors.